Study of Factors Affecting the Formation of Crystalline Hydrates in Gas Transportation - Gurbanov, A.N.; Sardarova, I.Z.; Aliyev, J.R. (Herald of Azerbaijan Engineering Academy, 2025)
In this article, changing the concentration of NaCl in solution affects the rate of hydrate formation only slightly. However, a further increase in the NaCl content in the solution reduces the rate of hydrate formation by 25%. In aqueous solutions with low concentrations of alcohols, the formation of mixed air and chloroform hydrate and propane hydrate is accelerated. It has been established that in the presence of small additions of alcohols, the mechanism of hydrate growth is similar to that observed for the growth of hydrates with the addition of surfactants. This effect manifests itself at the stage of mass crystallization. The process of hydrate formation is exothermic, therefore, to increase the rate of hydrate formation, it is necessary to intensively remove heat from the gas-water system. In experiments conducted under static conditions, this excess was about 0.3 MРa.